Pengaruh Akuntabilitas, Transparansi, Partisipasi masyarakat dan Kompetensi aparatur terhadap Pengelolaan Dana Desa - Umu Salamah Leisubun; Muhamad Rifandi (Program Studi Akuntansi Unimuda Sorong, 2025)
This research examines the effect of accountability, transparency, community participation, and the competence of village officials on the management of village funds in Kei-Kecil Timur District, Southeast Maluku Regency. The background of this study lies in the urgency of implementing transparent and accountable governance to strengthen development and improve community welfare. The novelty of this research is its focus on integrating governance principles with the utilization of the Village Financial System (SISKEUDES) in a regional context that has rarely been studied. A quantitative approach was applied through a survey of 72 respondents, consisting of village heads, secretaries, treasurers, and 15 members of the Village Consultative Body (BPD) from each of the 18 villages, selected using purposive sampling. The results indicate that all independent variables have a positive influence on village fund management. These findings suggest that effective village financial governance requires competent officials, transparent public information, and active community involvement. The study provides practical implications for village governments and stakeholders in improving the quality of village fund governance.